The Development of Germination Tests and Breaking Dormancy Techniques of Bitter Seeds (Andrographis paniculata (Burm. f.) Wall. ex Nees) - Gundala, Belangie Tuahte; Widajati, Eny; Ilyas, Satriyas (Journal of Tropical Crop Science, 2023)
Bitter seed (Andrographis paniculata (Burm. f.) Wall. ex Nees) is a medicinal species used in phyto pharmacy and known as ‘the king of bitterness’. Bitter seeds contain andrographolide, a diterpenoid lactone which is widely used in Indian medicine for snake bites and for the treatment of hepatitis. The research was conducted at the Seed Management Unit experimental field of the Indonesian Spice and Medicinal Plants Research Institute (IMACRI) and at the Seed Quality Testing Laboratory of IPB University, Indonesia, from January until May 2021. The objectives of the study is to determine the best germination test and effective breaking dormancy techniques to increase the germination percentage of bitter seeds. The study was arranged in a completely randomized design with two-factors. The first factor was seed treatments, i.e., control/untreated, chemical scarification with 5% H2SO4 for 10 minutes, and 5% H2SO4 followed by a 100 ppm GA3 soaking treatment. The second factor conducted was germination test methods according to International Seed Testing Association, i.e., germinating the seeds on the top of paper and in pleated paper. Our study demonstrated that seed treatment with H2SO4 can break seed dormancy and speed up seed germination. Bitter seed germination on the pleated paper was higher than with the top-of-paper method. Bitter seed germination with the top-of-paper method was at 65 DAS and the final germination was at 80 days after sowing (DAS), and the final germination was 55.2%. With the pleated paper method, the seeds germinated at 30 DAS and the final germination was at 70 DAS, and the final the germination of 59.2%.